(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The method used during the teaching of physical exercise or to solve another pedagogical task (open physical ability, facilitate its acquisition), for example, in the development of physical abilities, the following are taken into account, firstly, the expected effect from physical exercise, that is, with this exercise to decide what tasks (education, training, or health); secondly, the structure of physical exercise, whether it is static or dynamic exercise, cyclic, acyclic movement or other; thirdly, the possible methods of repetition (whether it is appropriate to train in parts or by performing the exercise in full, whether it is necessary to apply active rest between repetitions or whether passive rest can be provided, etc.). This characteristic of physical exercises allows to choose physical training tools and methods to solve the pedagogical tasks.